Solve for n 4n-3=-2n+9

Math
4n-3=-2n+9
Move all terms containing n to the left side of the equation.
Tap for more steps…
Add 2n to both sides of the equation.
4n-3+2n=9
Add 4n and 2n.
6n-3=9
6n-3=9
Move all terms not containing n to the right side of the equation.
Tap for more steps…
Add 3 to both sides of the equation.
6n=9+3
Add 9 and 3.
6n=12
6n=12
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6n=12 by 6.
6n6=126
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6n6=126
Divide n by 1.
n=126
n=126
Divide 12 by 6.
n=2
n=2
Solve for n 4n-3=-2n+9

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top